A formação inicial do professor de ciências da natureza e o uso de tecnologias de informação e comunicação (TIC): o que indicam os projetos pedagógicos de curso das licenciaturas no estado do Mato Grosso do Sul - Silva, Aline Ribeiro (2023)
In this research, the Pedagogical Course Projects (PPCs) of undergraduate courses in the area of Natural Sciences were analyzed (Biological Sciences, Physics and Chemistry) of the public universities of Mato Grosso do Sul, in person and distance learning modalities. The aim was to verify what is proposed in relation to Information and Communication Technologies (TIC), as well as to identify which theoretical, political, cultural and legal bases guide the PPCs analyzed. This is a case study with a qualitative approach (BOGDAN; BIKLEN, 2013), based on a documental analysis (LÜDKE; ANDRÉ, 2020), covering three stages: a) Bibliographical survey in Scielo databases, Theses and Dissertations bank by Capes (BTD) and Google Scholar; to check which studies cover this topic b) Collection of PPCs in the electronic portals of Higher Education Institutions (IES); c) Data analysis and categorization according to the guidelines proposed by Bardin (2013). This study was based on the PPCs made available before the implementation of the BNC Formation, in which they were collected from 2021 to 2022. As for the profile of the egress, twelve of the PPCs of the courses indicate that the graduate must be prepared for the use of TIC in their professional practice, as defined by the National Curriculum Guidelines (DCNs) for undergraduate courses in physics, chemistry and biology. However, of the twenty courses analyzed, only eight have disciplines that include TIC in their curriculum. The disciplines offered were identified according to their nature (compulsory or optional), workload, offer period and bibliography. From the categorization of the collected information, it was observed that the discussion about TIC in the initial training of science teachers is mostly focused on Distance Education (EaD) themes, addressing its history, legislation and tools for its mediation, virtual learning environments (AVA). However, it was verified from the summary and the indicated bibliographies that approaches on the articulation of TIC with specific themes of the course are scarce. Even indicated in the DCNs, the articulation of teacher training and TIC is not present in all the analyzed documents. From the research carried out, it is understood that simply increasing the workload or adding subjects that cover TIC is not enough for critical and reflective training, since the discussion may only privilege its use as a tool. Linked to these possible changes, there must also be a consolidated conception of the theoretical-methodological bases that will guide its discussion regarding the economic, political, social and cultural context in which it is inserted.